Instrument to determine needs of parental knowledge about adolescence and its management - Grettel Águila Calero; José Aurelio Díaz Quiñones; Paula Maribel Díaz Martínez; Nicolás Ramón Cruz Pérez (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2016)
Foundation: In adolescent positive parenting is fundamental to prevent complications. In this sense, it is required a scientifically supported instrument which identify precisely parents needs of knowledge as a leading figure in the management of this period and allows designing posterior orientation strategies. Objective: To develop an instrument for determining parents needs of knowledge about adolescent management. Methods: A study of technological innovation was developed for designing and validating an instrument directed to parents, adolescents and teachers. As main methods for the validation of our proposal there were considered Validity of Content (Moriyama Criteria), of criteria (expert criteria) and of construct (pilotage). Results: It was designed an instrument with content adjusted to the items established by Moriyama according to the 90.0 % of the consulted specialists, with a very satisfactory evaluation by the criteria of 17 experts, through evaluation rounds. In addition it was evaluated as a construct through a pilotage, which corresponded to the empirical research findings. Conclusion: The instrument called Adolescente. Parents knowledge needs about its management was scientifically validated. It integrates cognitive, affective, volitional and evaluative aspects concerning adolescents, which are necessary for parents' orientation, scientific approximation which developed for the first time in our environment and which may become a feasible, useful and applicable instrument for daily life.